2021
DOI: 10.1002/anie.202014425
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Conjugate Addition of Chiral Secondary Borylalkyl Copper Species

Abstract: We report the diastereo‐ and enantioselective conjugate addition of chiral secondary borylalkyl copper species derived from borylalkenes in situ to α,β‐unsaturated diesters. In the presence of a chiral bisphosphine‐ligated CuH catalyst, the conjugate addition provides a direct access to enantioenriched alkylboron compounds containing two contiguous carbon stereogenic centers in good yield with high diastereo‐ and enantioselectivity (up to >98:2 dr, >99:1 er) by assembling readily available starting alkenyl rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…While conjugate addition of a few configurationally stable chiral alkyl metallic reagents with α-heterofunctionality as the nucleophiles 18 , 19 and 1,6-conjugate addition of allene-derived nucleophiles 20 represented successful conjugate reactions, we recently reported that catalytic alkenylboron-derived copper nucleophiles could be utilized to accomplish diastereo- and enantioselective conjugate addition of α-borylalkyl copper species (Fig. 1c ) 21 . Inspired by this work, we envisioned a non-radical strategy for asymmetric assembly of two prochiral alkenes with stereocentre formation between the two connecting carbons bearing no heteroatom substituents (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While conjugate addition of a few configurationally stable chiral alkyl metallic reagents with α-heterofunctionality as the nucleophiles 18 , 19 and 1,6-conjugate addition of allene-derived nucleophiles 20 represented successful conjugate reactions, we recently reported that catalytic alkenylboron-derived copper nucleophiles could be utilized to accomplish diastereo- and enantioselective conjugate addition of α-borylalkyl copper species (Fig. 1c ) 21 . Inspired by this work, we envisioned a non-radical strategy for asymmetric assembly of two prochiral alkenes with stereocentre formation between the two connecting carbons bearing no heteroatom substituents (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As a model reaction for investigation, the underdeveloped Cu-catalysed conjugate addition with 1,1-diborylmethane to an α,β-unsaturated ketone substrate was selected. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Beginning with the enantioenriched product 3w , a diastereoselective reduction of the keto group with sodium borohydride , and a subsequent cyclization provided lactone 4 in good yield as a 10:1 mixture of diastereomers. The anti -lactone 5 was successfully obtained via a Krapcho decarboxylation . Finally, the Ru-catalyzed oxidative cleavage of the alkenyl moiety yielded carboxylic acid 6 , which can be transformed to (+)-methylenolactocin using a literature method …”
mentioning
confidence: 99%